EFFECT OF ETHANOLIC RED CABBAGE EXTRACT ON OXIDATIVE STRESS IN HYPERTHYROID RABBITS INDUCED BY LTHYROXINE - Majeed, Mohaned; Al-Azzawie, Hassan (Iraqi Journal of Science, 2024)
The protective effect of red cabbage extracts against hyperthyroid induced by Lthyroxinein male rabbits was studied. Forty animals were divided randomly intofour groups. Group A: Healthy rabbits, Group B: Healthy rabbits received (100mg/kg.b.w) red cabbage extract, Group C: hyperthyroid rabbits were given an oraldose of (20μg/kg b.w) L-thyroxine once daily for four weeks to inducehyperthyroidism and group D: hyperthyroid rabbits received red cabbage extract. Atthe end of the experiment, blood samples were taken for biochemical analysis. Theobtained results revealed that hyperthyroid rabbits induced by L-thyroxine hadsignificant increase(P<0.01) in serum levels of triodothyronine (T3), Thyroxine(T4), lipid peroxidation marker malondialdehyde (MDA), as well as significantdecrease in reduced glutathione (GSH), glutathione peroxidase (GPX), superoxidedismutase (SOD) and catalase (CAT) enzymes, compared to the normal controlgroup. Oral administration red cabbage extract caused significant reduction in serumlevels of T3, T4 as well as MDA and produced significant increase in thyroidstimulating hormone (TSH), GSH, GPX, SOD and CAT, compared to the positivegroup. Red cabbage treatment suppresses the hyperthyroidism-induced oxidativedamage. These results suggest that experimental hyperthyroidism is accompaniedwith increased oxidative stress and with the consumption of antioxidant enzymes ininduced oxidative aggressions. A protective effect of red cabbage extract onoxidative stress induced by excessive administration of thyroid hormones weredetected and for the first time anti hyperthyroid activity was observed.